Adsorbing Colloid Flotation Of Arsenic In The Presence Of Aluminum Sulfate - M. K. Aydogan (International Mineral Processing Congress, 2012)
Today, arsenic has become a much greater problem than before because of the limitations introduced by WHO and USEPA that are lowered from 0.05 ppm to 0.01 ppm. In the nature Arsenic is mostly found as inorganic compounds in the forms of arsenite (As+3) and arsenate (As+5) in aqueous solutions. Arsenic contamination in ground and surface waters has been encountered in almost every country. This element has a carcinogenic effect and can occur in natural sources and anthropogenic sources such as metal mining, groundwater usage and industrial activities. In this study adsorbing colloid flotation was applied in the presence of aluminum sulfates. In the experiments SDS and K-Oleate were used as collectors while MIBC was the frother employed. The effects of collectors and aluminum/arsenic ratios on the removal of arsenic were examined under various pH values. It was found that arsenic removal enhanced with increasing aluminum concentration. Furthermore, it was observed that pH was a very critical parameter in all experiments. The best results were obtained when initial As: SDS: Al concentrations were 10:40:40 ppm at pH 5.5. At this concentration, the efficiency of arsenic removal found to be 99.9%. Keywords: arsenic, adsorbing colloid flotation, aluminum sulfate